Sexuality Among Adolescents and Young Adults With Intellectual Disability: Knowledge, Attitude, and Practices. Issue 2 (April 2021) - Chavan, Bir Singh; Ahmad, Wasim; Arun, Priti; Mehta, Shivangi; Nazli,; Ratnam, Vani; Raina, Deepti
Context: It is generally believed that persons with intellectual disability (PWID) do not have sufficient knowledge about sex and sexuality. As there is not much published work from India, such an attitude of clinicians and caregivers appears more to be an assumption. The scant information from other countries on sex and sexuality of the PWID cannot be generalized to India because of cultural differences. Aims and Objectives: The study was conducted to find out knowledge, attitude, and sexual practices among persons with mild intellectual disability (ID). Settings and Design: Thirteen participants with DSM-5 diagnosis of mild ID (intellect quotient [IQ] between 50 and 69) in the age ranging from 16 to 27 years (mean IQ and age was 56.69 and 21.0, respectively) were selected from the Government Rehabilitation Institute for Intellectual Disabilities, Chandigarh. For this study, exploratory method using focus group discussion (FGD) was used. Data was collected using qualitative method of FGD. Results: The results showed that persons with mild ID have knowledge about sex and sexual practices and they are sexually active and are indulging in sexual acts. Conclusion: Based on the findings derived from this research, it is concluded that PWID have knowledge and skills to experience sexual activities. However, findings of this study are limited to only persons with mild ID (IQ: 50-69). Need to sensitize and provide appropriate sexual health care for persons with ID are discussed.